Advancing UAV Video Transmission: A Full-Duplex System with RF and Signal Processing for Reliable, Long-Range HD Communication - Pratik Banmeru; Namrata Patole; Atul Kumar; Durga Sawant (International Journal of VLSI Circuit Design & Technology, 2024)
Unmanned aerial vehicles (UAVs) have transformed industries by enabling advanced aerial imaging and data collection. However, transmitting high-definition (HD) video from UAVs to ground stations poses challenges such as limited range, bandwidth constraints, and interference. This paper presents the development of an HD, full-duplex video transmission system using cutting-edge electronic technologies, including advanced radio frequency (RF) systems and signal processing. These electronic systems are designed to ensure fast, reliable, and interference-free video transmission over long distances. The research explores key electronic concepts such as full-duplex communication, channel modeling, signal processing techniques, and interference cancellation, which are critical for building efficient UAV video transmission systems. The research also explores key electronic principles, such as channel modeling, which simulates how signals travel through the air, and interference cancellation, which helps eliminate overlapping signals. These technologies work together to improve the performance of the video transmission system, ensuring it remains efficient and reliable in challenging environments. Overall, this paper highlights the importance of integrating advanced electronics and communication systems to overcome the challenges of drone video transmission, paving the way for more effective and versatile UAV applications.
Keywords: AD9361; Camera; Zedboard@7000; radio frequency (RF); wideband dipole antenna